Overexpression of GILZ in macrophages limits systemic inflammation while increasing bacterial clearance in sepsis in mice. Issue 4 (16th January 2020) - Ellouze, Mehdi; Vigouroux, Lola; Tcherakian, Colas; Woerther, Paul‐Louis; Guguin, Aurélie; Robert, Olivier; Surenaud, Mathieu; Tran, Thi; Calmette, Joseph; Barbin, Thomas; Perlemuter, Gabriel; Cassard, Anne‐Marie; et al.
Abstract: Studies support the beneficial effects of glucocorticoids (GCs) during septic shock, steering research toward the potential role of GC‐induced proteins in controlling excessive inflammatory responses. GILZ is a glucocorticoid‐induced protein involved in the anti‐inflammatory effects of GCs. We investigated whether the overexpression of GILZ specifically limited to monocytes and macrophages (M/M) alone could control inflammation, thus improving the outcome of septic shock in animal models. We also monitored the expression of GILZ in M/M from septic mice and septic‐shock patients. M/M from patients and septic mice displayed significantly lower expression of GILZ than those isolated from controls. Furthermore, transgenic mice (Tg‐mice) experiencing sepsis, with increased expression of GILZ restricted to M/M, showed lower frequencies of inflammatory monocytes than their littermates and lower plasma levels of inflammatory cytokines. Tg‐mice also had lower blood bacterial counts. We further established that the upregulation of GILZ in M/M enhanced their phagocytic capacity in in vivo assays. The increase of GILZ in M/M was also sufficient to improve the survival rates of septic mice. These results provide evidence for a central role of both GILZ and M/M in the pathophysiology of septic shock and a possible clue for the modulation of inflammation in this disease. Abstract : GILZ is an immune system regulator. We demonstrate a new role for GILZ in septic shock, showing that GILZ expression limited to monocytes/macrophages is sufficient to hamper the systemic inflammatory response in vivo, while containing bacterial spread. Hence, we show that immunomodulation can lead to anti‐inflammatory effects without immunosuppressive effects.